2017
DOI: 10.1111/efp.12375
|View full text |Cite
|
Sign up to set email alerts
|

Ceratocystis platani is killing plane trees in Istanbul (Turkey)

Abstract: Summary Ceratocystis platani was detected at several locations in the European side of Istanbul, causing severe dieback and mortality, mainly on Platanus × acerifolia imported from Italy approximately 160 years ago, but also on Platanus orientalis. In the work reported here, the causal agent of the dieback and mortality was identified based on morphological characteristics in culture and internal transcribed spacer (ITS) sequencing, confirming the presence of C. platani in Turkey. All analysed C. platani isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Xylella fastidiosa is a bacterium reported on more than 350 different hosts (Denancè et al 2017) and since 2013 is responsible for Olive Quick Decline Syndrome in Southern Italy (Apulia) (Saponari et al 2013), more recently it has been found in Tuscany (Central Italy) (EPPO 2019); Ceratocystis platani is an ascomycetous fungus reported as the causal agent of Canker Stain Disease (CSD) of plane tree ( Platanus ) in urban and natural ecosystems (Lehtijärvi et al 2018; Tsopelas et al 2017). Phytophthora ramorum is an oomycete causing Sudden Oak Death (SOD) in the USA (Rizzo et al 2002) but the pathogen has also been found in European ornamental nurseries (Werres et al 2001) and in plantations of Japanese larch ( Larix kaempferi ) in Great Britain (Brasier and Webber 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Xylella fastidiosa is a bacterium reported on more than 350 different hosts (Denancè et al 2017) and since 2013 is responsible for Olive Quick Decline Syndrome in Southern Italy (Apulia) (Saponari et al 2013), more recently it has been found in Tuscany (Central Italy) (EPPO 2019); Ceratocystis platani is an ascomycetous fungus reported as the causal agent of Canker Stain Disease (CSD) of plane tree ( Platanus ) in urban and natural ecosystems (Lehtijärvi et al 2018; Tsopelas et al 2017). Phytophthora ramorum is an oomycete causing Sudden Oak Death (SOD) in the USA (Rizzo et al 2002) but the pathogen has also been found in European ornamental nurseries (Werres et al 2001) and in plantations of Japanese larch ( Larix kaempferi ) in Great Britain (Brasier and Webber 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although some plant pathogen species in the three fungal genera Botryosphaeria, Neopestalotiopsis and Diaporthe are known to cause important diseases in plants, many species are also recorded commonly as endophytes and saprotrophs. (Maharachchikumbura et al, 2014;Slippers & Wingfield, 2007;Udayanga et al, 2014 (Lehtijärvi et al, 2018) suggests that this situation may be occurring there: it is possible that the trees sampled in the present…”
Section: Discussionmentioning
confidence: 89%
“…work were already attacked by C. platani. Isolation of the wilt/canker stain pathogen, however, requires specialized methods(Lehtijärvi et al, 2018) compared with the pathogens described in this paper.Wilt-causing pathogens, including Ceratocystis spp., cause staining in affected xylem; the plant responses to problems in the xylem include production of tyloses or gums/gels to occlude the damaged parts but with virulent pathogens, the occlusions can cause failure of the whole xylem system in the infected tree. Despite these issues, wilt pathogens do not always kill the host plants.…”
mentioning
confidence: 99%
“…Ceratocystis is a fungal genus with several species that cause rot diseases of agricultural crops and vascular wilt and canker stain of woody plants Harrington 2013), though application of the term vascular wilt to diseases caused by Ceratocystis and related species is controversial (Kile 1993). A typical vascular wilt pathogen such as Fusarium or Verticillium moves through the xylem but does not invade xylem parenchyma or ray cells until the host metabolism is disrupted and the tissues surrounding xylem vessels die (Talboys 1972 (Morris et al 1993;Lehtijärvi et al 2018). Ceratocystis species invade their hosts through wounds, which may be caused by human activity, other mammals such as monkeys, elephants and squirrels, wind or boring insects (Harrington 2007;Tarigan 2011b).…”
Section: Biology and Disease Dynamicsmentioning
confidence: 99%